Effect of Micro-encapsulated Synbiotic at Different Frequencies for Luminous Vibriosis Control in White Shrimp (Litopenaeus vannamei) - WAODE MUNAENI; MUNTI YUHANA; WIDANARNI WIDANARNI (Indonesian Society for microbiology, 2014)
The aim of this study was to evaluate the effect of micro-encapsulated synbiotic application at different frequencies for luminous disease control in white shrimp (Litopenaeus vannamei). The luminous disease is caused by Vibrio harveyi. In this experiment, a synbiotic which was a combination of the probiotic Bacillus sp. NP5 RfR and the oligosaccharides from sweet potato (Ipomea batatas L.) jago variety was apllied. The synbiotic was encapsulated by spray drying method. The in vivo experiment was conducted by supplementing the shrimp’s diet with the micro-encapsulated synbiotic for 40 days. Treatments included the administration micro-encapsulated synbiotic in different frequencies i.e. once a week (A), twice a week (B), daily (C), and without micro-encapsulated synbiotic (control treatment). The control treatment consisted of positive (K+) and negative (K-) controls. After 30 days period, all of the shrimp were challenged by intramuscular injection of pathogenic V. harveyi RfR at a concentration of 106 CFU ml-1 except the negative control. The treatment C resulted in significantly higher survival rate (SR), specific growth rate (SGR), and immune responses than those of the controls, whereas the feed conversion ratio (FCR) was lower than the controls. In addition, the population of Bacillus sp. NP5 RfR and total bacterial count (TBC) in the intestines increased, whereas the population of V. harveyi RfR and the total vibrio count (TVC) were lower compared to the controls.